Sistem E-Mentoring dalam Proses Pembelajaran di Perguruan Tinggi: Systematic Literature Review - Nurul Faizah; Ghasa Faraasyatul A’lam; Maisyaroh Maisyaroh; Ahmad Yusuf Sobri (Universitas Negeri Malang, 2023)
Abstract: The process of implementing supervision in higher education should include supervision of administrative and academic matters. Digital-based monitoring systems are also called e-monitoring by utilizing application-based services and websites. This is done so that the performance of supervisors in quality assurance agencies is more efficient and effective. This study aims to describe and analyze digital-based supervision or e-monitoring that has been developed and implemented by several universities in Indonesia in the supervision process. This study uses a systematic literature review. The results of the study show that several universities in Indonesia have used a supervisory process by utilizing technology to improve the quality of higher education in carrying out the Tri Dharma. Information technology as a surveillance medium developed on a website basis such as the Rapid Application Development (RAD) and Simple Additive Weighting (SAW) models utilizes Radio Frequency Identification (RFID) which has been integrated with the accounts of each academic community, including students, so that students can participate in monitoring and controlling the learning process. In addition to developing applications, leaders at tertiary institutions have begun to utilize applications available on the PlayStore to control lecturer performance in carrying out the Tri Dharma. The application used can provide information on lecturer performance in real time starting from lesson preparation, lecturer presence, progress in the process of preparing questions,to assessing student study results.Keywords: e-mentoring ;learning process; quality of education; higher educationAbstrak: Proses pelaksanaan pengawasan di pendidikan tinggi hendaknya mencakup pengawasan terhadap hal yang bersifat administratif dan akademik. Sistem monitoring berbasis digital disebut juga emonitoring dengan memanfaatkan layanan berbasis aplikasi maupun website. Hal ini dilakukan agar kinerja para pengawas dalam lembaga penjamin mutu lebih efisien dan efektif. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis pengawasan berbasis digital atau e-monitoring yang dikembangkan dan diterapkan oleh beberapa perguruan tinggi di Indonesia dalam proses pengawasan. Penelitian ini menggunakan systematic literature review. Hasil penelitian menunjukkan bahwa beberapa perguruan tinggi di Indonesia telah menggunakan proses pengawasan dengan memanfaatkan teknologi untuk meningkatkan kualitas perguruan tinggi dalam menjalankan Tri Dharma. Teknologi informasi sebagai media pengawasan yang dikembangkan berbasis website seperti model Rapid Application Development (RAD) dan Simple Additive Weighting (SAW) memanfaatkan Radio Frequency Identification (RFID) yang telah terintegrasi dengan akun masingmasing civitas akademik, termasuk mahasiswa, sehingga mahasiswa dapat berpartisipasi dalam pemantauan dan pengendalian proses pembelajaran. Selain mengembangkan aplikasi, para pimpinan di perguruan tinggi mulai memanfaatkan aplikasi yang tersedia dalam PlayStore untuk mengontrol kinerja dosen dalam melaksanakan Tri Dharma. Aplikasi yang digunakan dapat memberikan informasi kinerja dosen secara real time mulai dari persiapan pembelajaran, kehadiran dosen, kemajuan dalam proses penyusunan soal, hingga penilaian hasil studi mahasiswa.Kata kunci: e-mentoring; proses pembelajaran; kualitas pendidikan; pendidikan tinggi